Identificación de las barreras para acceder a la Política Pública del Bono de Desarrollo Humano en el Cantón Chinchipe, Provincia de Zamora Chinchipe - Jaramillo Rodríguez, Ana María (2024)
Around the world, quality of life has become a topic of social analysis and development research, focusing on the lack of resources of people below the poverty line to meet their basic needs such as food, education, housing, basic services and work. Faced with this problem, the Ecuadorian State seeks to improve the living conditions of its citizens through social policies, which is why it implements the BDH, which provides financial incentives to facilitate access to educational and health centers, measures that seek to protect families below the poverty line, provide them with well-being, as well as promote a better life in society. The general objective of the research was "Evaluate the barriers that the population of the Chinchipe canton has to access the Human Development Bonus." The deductive method was applied, because it starts from the observation of general facts about the main barriers to accessing the BDH, and then moves towards proposals that allow improving coverage for those who really need it. In this sense, this research has a quantitative approach that was used to collect and analyze data from the results of surveys of people in poverty and extreme poverty, information that is analyzed in order to draw conclusions and propose solutions. for the problem posed. Thus, we found as a result of this research that: people in poverty live with a family member or partner, have access to communication routes and many times the officials in charge of carrying out social records do not go to distant homes and separated from the rural sector due to lack of knowledge of the places and the difficulty of reaching them due to lack of transportation. From these results we can conclude the following: that the main barriers that prevent the population in situations of poverty and extreme poverty from receiving the benefit of the BDH is the geographical location of the Canton since there are not enough means of transportation. access, the lack of vehicles and public transportation blocks the visit of those in charge of collecting social records.